PKM DEVELOPMENT OF HEALTHY CULTURE OF TRADITIONAL MARKET TRADERS IN PULO BRAYAN VILLAGE, WEST MEDAN DISTRICT: PKM PENGEMBANGAN BUDAYA SEHAT PEDAGANG PASAR TRADISIONAL DI KELURAHAN PULO BRAYAN KECAMATAN MEDAN BARAT - Izzah Dienillah Saragih; Umi Salmah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Traditional market is a public space where it estimated more than 50 million people are actively involved. A dirty and slum market will become a place for infectious diseases to spread, especially during the COVID-19 pandemic. This community service aimed to  develop the SERASI Culture (Sehat, Rapi, and Bersih) among community. It located at Traditional Market Pulo Brayan, West Medan District. Using participatory from the community,  the activities are (1) health promotion (2) providing masks (3) making a mechanical sink and (4) educating hand washing with soap. The results showed the excitement of the community and the established of two sink near the market to facilitate. The sustainability of this service activity was marked by the formation of a cadre of SERASI cultural movers from market traders who will collaborated with the local institution and Universitas Sumatera Utara. Creating pocket books which will distributed and to maintain the sanitation facilities for the sustainability of their functions are plans for future achievements of this community services